ANALISA TINGKAT EFISIENSI PENGGUNAAN KEUANGAN DITINJAU DARI RASIO ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA KANTOR CAMAT KALIDONI - PALEMBANG TAHUN 2012-2014 - Jamiyla Jamiyla; Bernika Ifada Puti Nz; Endah Meiria (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this study is to determine Budget and Expenditure realization at the Kalidoni District Office in Palembang. Variable of this study was realization of Budget and Expenditure during 2012-2014. The subjects are the  Budget and Expenditure at the Kalidoni District Office in Palembang. The method of this study was descriptive methods and data collection techniques were documentation and  interviews.The data source of this study were the employees at Kalidoni District Office. The results of  this study indicate that the realization of Budget and Expenditure District of Kalidoni Palembang, the ratio of income and unstable realization were 96% in 2012, 58% in 2013 and 85% in 2014. For the ratio of budget and realization in 2012 of 85%, in 2013 by 88% an d in 2013 is 92%. The ratio of expenditure and realization were 89% in 2012, 68% in 2013 and 472% in 2014. The independence ratio were 110% in 2012, 203% in 2013 and 714% in 2014. Effectiveness ratio were 91% in 2012, 66% in 2013 and 9,8% in 2014. Efficiency ratio were 70% in 2012, 72% in 2013, and 87% in 2014. In general, the realization of  the budget and expenditure in Kalidoni district is good enough, the level of independence is good, but the level of effective and efficient in the District Kalidoni is still not included in the criteria. Keywords: Realization, Budget and Expenditure